The bone mineral content alterations in pediatric patients medicated with levetiracetam, valproic acid, and carbamazepine - Serin, Hepsen Mine; Koc, Zehra Pinar; Temelli, Berfin; Esen, Ihsan (Academic Press Inc Elsevier Science, 2015)
Aim: The negative effect of antiepileptic drugs on bone health has been previously documented. However, which antiepileptic drug is safer in regard to bone health is still questionable. Our aims were to investigate the bone mineral density alterations in pediatric patients who receive antiepileptic medication for a minimum of two years and to compare the results of these drugs. Materials and methods: Fifty-nine patients (32 males, 27 females; mean age: 8.6 +/- 4.6 years) and a control group (13 males, 7 females; mean age: 7.6 +/- 3.3 years) were included in the study. The patients were receiving necessarily the same antiepileptic drugs (AEDs) for at least two years, and none of the patients had mental retardation or cerebral palsy. The patients were divided into three groups: group 1 (patients receiving levetiracetam (LEV), n = 20), group 2 (patients receiving carbamazepine (CBZ), n = 11), and group 3 (patients receiving valproic acid (VPA), n = 28). Plasma calcium (Ca), phosphorus (P), parathyroid hormone (PTH), alkaline phosphatase (ALP), vitamin D levels, and bone mineral density (BMD) values of femur and vertebras (L1-4) and z-scores (comparative results of BMD values of the patients with the age-and gender-matched controls in device database) of the groups were compared. Results: The differences between P, PTH, ALP and age, Ca and BMD results, and vitamin D levels of the patients in all four groups was not statistically significant according to Kruskal-Wallis test (p > 0.05). The z-score levels of all the patient and control groups were also not statistically significantly different compared with each other. Conclusion: In contrast to previous reports in pediatric patients, our study has documented that there is not a considerable bone loss in patients receiving long-term AED medication. Although levetiracetam has been proposed as bone-protecting medication, we did not observe any difference between AEDs regarding bone mineral density after two years of treatment. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Antiepileptic drugs; Children; Bone mineral density; Levetiracetam; Carbamazepine; Valproic acid